Documentation errors in instrumentation and electrical systems: Toward productivity improvement using System Information Modeling - Love, Peter; Zhou, Jingyang; Sing, Michael; Kim, Jeong (Elsevier BV, 2013)
Documentation errors have been identified as a significant problem within the construction and engineering industry. Errors contained with contract documents can contribute to loss of profit, reduced productivity, and cost and time overruns as well as contractual disputes. Research has identified that as much as 60% of variations in construction and engineering projects are a result of errors and omissions contained within poor quality documentation. Considering this alarming statistic and the impact that poor quality documentation can have on productivity, the research presented in this paper classifies and quantifies errors in 106 drawings and the cable schedule used to document for the electrical package for an Iron Ore Stacker Conveyor. The research reveals that Computer Aided Design (CAD) used to produce the electrical drawings was ineffective, inefficient and costly to produce as they contained an array of errors. In addressing the need to eliminate documentation errors and improve productivity, the cable schedule is used to create a Systems Information Management to develop a 1:1 object orientated model using the software Dynamic Asset Documentation. As a result, of using this approach it is estimated that a 94% cost saving and a substantial improvement in productivity could have been attained in this particular case.